Detection of Biofilm Formation by Staphylococcus aureus Isolated from some Respiratory Tract Infections (Journal of the College of Basic Education, 2025)
Staphylococcus aureus is a significant pathogen involved in respiratory tract infections (RTIs), and its ability to form biofilms significantly contributes to its persistence and resistance to treatment. This study aimed to evaluate the biofilm-forming capacity of S. aureus isolates from RTIs using two phenotypic methods. A total of 55 isolates were collected from respiratory specimens, from different hospitals in Baghdad. Identification was performed using phenotypic characteristics, biochemical tests, and the VITEK 2 system. Biofilm formation was assessed using Congo red agar and the microtiter plate assay (MTP). According to Congo red, 43.63% of isolates were strong biofilm producers, 47.27% intermediate and 9.09% non-producers, whereas the MTP showed 40% strong, 38.18% moderate, and 21.81% weak producers. Notably, all isolates demonstrated some level of biofilm formation by the MTP. These findings highlight the widespread presence of biofilm-forming ability among S. aureus isolates from RTIs and underscore the potential role of biofilms in treatment resistance and infection persistence. Consequently, there is a need to develop novel therapeutic strategies that target biofilm eradication.